Salinity Induced Antioxidant Defense in Roots of Industrial Hemp (IH: Cannabis sativa L.) for Fiber during Seed Germination - Naveen Dixit (MDPI AG, 2022)
Global climate change induced sea level rise, rainfed agriculture, poor quality irrigation water, and seawater intrusion through interconnected ditches and inland waterways cause soil salinity in inland and coastal areas. To reclaim and prevent further soil erosion, salt tolerant crops are required. Industrial Hemp (IH: Cannabis sativa L.) is used for food, fiber, and medicinal purposes throughout the world. In spite of that, little is known about the salt tolerance mechanisms in IH. Seed germination and development of the roots are the primary events in the life cycle of a plant, which directly interact with soil salinity. Therefore, in vitro germination experiments were conducted on the roots of 5-day-old seedlings using four varieties (V1: CFX-2, V2: Joey, V3: Bialobrzeskie, and V4: Henola) of IH for fiber. Five salinity treatments (0, 50, 80, 100, 150, and 200 mM NaCl) were used to screen the IH varieties on the basis of I: seed germination percent (SGP), II: quantitative morphological observations (root length (RL) and root fresh weight (RFW)), III: oxidative stress indices (hydrogen peroxide (H2O2) and lipid peroxidation), and IV: antioxidant defense system comprises of superoxide dismutase (SOD), catalase (CAT), guaiacol peroxidase (GPOD), ascorbate peroxidase (APOD), glutathione reductase (GR). The varieties V1 and V3 showed salt tolerance up to 100 mM by maintaining higher SGP, less reduction in RL and RFW. These roots in V1 and V3 showed lower levels of H2O2 and lipid peroxidation by displaying higher activities of SOD, CAT, GPOD, APOD, and GR while a reciprocal trend was observed in V4. However, roots in V2 showed higher activities of antioxidant enzymes with lower levels of H2O2 and lipid peroxidation, but showed declines in RL and RFW at 80 mM NaCl onward. Roots in V4 were the most susceptible to NaCl stress at 50 mM and onward.